An unfulfilled relationship: US–Burma/Myanmar political relations - Lubina, Michał (Asia in World Politics: Past, Present, and Future, 2021)
The main goal of this article is to examine policy of the United States towards Burma from the perspective of political science. First part of analysis is dedicated to political ties between Washington and Rangoon (later: Naypyidaw) till 1988 when mass demonstrations took place in Burma. Further, article concentrates on period between 1988 and 2011, when Myanmar has been criticized by the US over violation of human rights. Author points out that situation has changed in 2011 when Washington shifted its policy towards Myanmar from isolationism to engagement under Obama’s administration but Burma has been neglected once again with Trump’s coming to power, when bilateral relations were overshadowed by Rohingya crisis. On the basis of these factors, Author concludes that the US-Myanmar relations will remain unfulfilled for the next years.